2011
DOI: 10.3389/fpsyg.2011.00180
|View full text |Cite
|
Sign up to set email alerts
|

Authentic and Play-Acted Vocal Emotion Expressions Reveal Acoustic Differences

Abstract: Play-acted emotional expressions are a frequent aspect in our life, ranging from deception to theater, film, and radio drama, to emotion research. To date, however, it remained unclear whether play-acted emotions correspond to spontaneous emotion expressions. To test whether acting influences the vocal expression of emotion, we compared radio sequences of naturally occurring emotions to actors’ portrayals. It was hypothesized that play-acted expressions were performed in a more stereotyped and aroused fashion.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(73 citation statements)
references
References 39 publications
1
71
0
1
Order By: Relevance
“…The modulation in the TTG is indicative of an influence on early cortical auditory processing (Arnott, Binns, Grady, & Alain, 2004), likely due to differences in acoustic features between authentic and play-acted stimuli (Jürgens, Hammerschmidt, & Fischer, 2011). Therefore, the direct influence of authenticity on activation appears to be a spontaneous response to contextual differences between stimuli, particularly when participants are not told about authenticity or do not have to explicitly determine authenticity.…”
Section: Discussionmentioning
confidence: 99%
“…The modulation in the TTG is indicative of an influence on early cortical auditory processing (Arnott, Binns, Grady, & Alain, 2004), likely due to differences in acoustic features between authentic and play-acted stimuli (Jürgens, Hammerschmidt, & Fischer, 2011). Therefore, the direct influence of authenticity on activation appears to be a spontaneous response to contextual differences between stimuli, particularly when participants are not told about authenticity or do not have to explicitly determine authenticity.…”
Section: Discussionmentioning
confidence: 99%
“…Because we recorded animals in natural contexts, it was essential to use also for human stimuli spontaneously produced vocalizations recorded in natural contexts (also because studies already showed differences in the vocal production as well as in the perception of play-acted and authentic vocalizations [47], [48]). We chose vocalizations of human infants as human stimuli because adults will be aware that they are being recorded.…”
Section: Methodsmentioning
confidence: 99%
“…For example, to what extent does emotional resonance depend on distinguishing between normal courtesies and pleasantries conveyed in social interactions and specific affective responses contingent on reactions to the qualities of a product/service offering or to what a customer boundary spanner says and how he or she says it as part of a persuasive communication? Research on visual and verbal emotion authenticity may provide insights here (e.g., Jurgens, Hammerschmidt, & Fischer, 2011;Sebe et al, 2007).…”
Section: Discussionmentioning
confidence: 99%